Subtexte der Menschheitsgeschichte: Zur Literarisierung von Geschichtsphilosophie bei Immanuel Kant, Johann Gottfried Herder und Christoph Martin Wieland - Kuhn, Kristina (transcript, 2018)
Starting with the literary form of a »beytrag/contribution«, Kristina Kuhn questions the paradigm of a systematically enlightened philosophy of history around 1800.